L2 acquisition of Spanish dative clitics by English and Dutch learners - Escobar-Álvarez, M. Ángeles (Studies in Second Language Learning and Teaching, 2017)
This article examines the second language acquisition (SLA) of Spanish dative clitics in clitic doubling (CLD) structures that are closely related to the double object construction (DOC) in English and Dutch. It also addresses the question of how adult English and Dutch speakers learning L2 Spanish in a formal setting develop knowledge and use of the animacy constraint in the target language, which is different from the first language (L1) counterparts. The role of transfer in acquiring new syntactic structures has been taken into account, where dative clitics appear and animate objects are marked by the dative preposition ‘to.’ New findings are obtained on CLD and the Spanish animacy constraint from a grammaticality judgement task (GJT), completed by English and Dutch learners at B1 and B2 CEFR levels. The difficulties learners experienced were not always due to negative L1 transfer, but also related to the complexity of the argument structure where the clitic is inserted. This has clear implications for the teaching of pronominal elements which are closely related to different syntactic configurations in Spanish.